Penilaian Nilai Wajar Saham Pt Ciputra Development Tbk - Sheane, Sheane (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
An investor could invest by buying companies’ stocks. Therefore, it is crucial for investors to know the fair value of shares of a company to anticipate the risks and benefits. The fair value of shares reflects the value of that company. This research is aimed to assess the fair value of shares of PT. Ciputra Development Tbk, whether its value is above or below the market price. This research was conducted using secondary data, which are the company’s prospects, yearly report, and other official publication. Quantitative analysis was chosen to process and analyse the data collected. Method used in this valuation is the Discounted Cash Flow method with Free Cash Flow to Firm model and Relative Valuation with Price Earnings Ratio model. The result of the valuation would be useful to be used as the basis for decision making on investing, whether to buy, hold or sell the stock. Based on the calculated stock value, it was obtained that the fair value of shares of PT. Ciputra Development Tbk, using discounted free cash flow to firm method, is Rp 1.092,- which means the stock price of PT. Ciptura Development Tbk is over the market price or overvalued in comparison to its intrinsic value. On the other hand, using price earning ratio as the chosen method shows that the fair value of shares is Rp. 1.262,4 per stock which means the price of PT. Ciputra Development Tbk stock is under the market price or undervalued towards its intrinsic value.